Interpretações de estudantes surdos sobre suas experiências de estudo durante a pandemia - Lima, Marta de Souza (Brasil, 2024)
The year 2020 was a typical year for humanity, which found itself hit by a pandemic caused by the Covid-19 vírus. Several aspects of life in society have been modified, and education is no different. Schools in Brazil began to operate remotely, in order to avoid direct contact between people. Classes began to be carried out remotely, a context that changed the reality of students and teachers. Therefore, this research is dedicated to analyzing the meanings attributed by deaf students to the remote teaching modality, addressing the pedagogical, social and economic challenges of implementing a distance education proposal in a context of unequal access, such as Brazil. Seven semi-structured questions were asked to three students from the Letters-Libras Degree Course at UFAM, which were subjected to interpretative analysis. The data demonstrate that deaf students were faced with the challenge of being able to follow classes, given the specificities of their learning processes, the resulting support needs and the difficulties in adapting to digital information and communication tools.